“Anonymous collectivity” and “sly civility”: postcolonial defiance in a satirical short story by Aziz Nesin - Mehrvand, Ahad; Khorsandi, Javad (Penerbit Universiti Kebangsaan Malaysia, 2018)
Until a few years ago, Turkey was usually seen as irrelevant to colonial studies owing to its non-colonial status. More recently, however, there has been a more flexible approach to considering the possibility of studying modern Turkey under the heading of postcolonial studies. By acknowledging the socio-political similarities between Turkey and colonized countries, the current study employs a postcolonial framework to analyze a short story by a Turkish author. In doing so, Aziz Nesin’s “Don’t you have any Donkeys in your Country?” is studied to show how Nesin contributes to the political and socio-economic status of Modern Turkey and the highlighted controversy over the applicability of postcolonial perspectives to the Turkish context. The present study draws upon Albert Memmi’s notion of “anonymous collectivity” and Homi K. Bhabha’s “sly civility” as postcolonial means of indirect defiance, to identify the ways in which the narrative contributes to its contemporary milieu. We argue that throughout the story Nesin satirizes the so-called expert colonizer for his fundamentally false assumption about the naïveté of the colonized nation. The story reflects that although the Turkish peasant has unconsciously internalized the colonialist ideology of “anonymous collectivity,” the very same indirect means of defiance is consciously used by the peasant to overcome inequality and white supremacy in the sphere of selling Turkish carpets as one of the most prestigious products to the Western world. This study contributes to the literature on postcolonialism, first by raising the possibility of including modern Turkey in postcolonial studies, and then by examining Nesin’s response towards the postcolonial-like ideology whereby it is concluded that oppression creates contradictions in the ostensible colonized/colonizer, impairing and reversing both groups’ identity and humanity. We also conclude that the narrative reverses the dominant ideologies of clever and knowledgeable Americans by giving voice to a subaltern Turkish peasant whose goal is to resist the enduring effects of economic and cultural oppression.